Pemberdayaan Kelompok Informasi Masyarakat Oleh Dinas Komunikasi Dan Informatika Dalam Upaya Mendorong Diseminasi Informasi - Irianto, Winno Riskinda (Universitas Negeri Surabaya, 2023)
Indonesia's vast geographic location will cause an information gap, including in Mojokerto Regency. To overcome the information gap, the government formed a group engaged in the information sector so that information dissemination can be achieved. This group is called the Community Information Group or KIM. With the formation of KIM, empowerment needs to be carried out by the local government, especially the Mojokerto District Communication and Information Service so that KIM can run according to its duties. The purpose of this research is to find out how the KIM empowerment by the Mojokerto District Communication and Information Service is in an effort to encourage information dissemination. This study uses Wrihatnolo and Dwidjowijoto's Empowerment Theory which explains that empowerment includes 3 stages namely, the awareness stage, the capacity building stage and the empowerment stage. The results showed that the Mojokerto District Communication and Information Service carried out 3 stages of empowerment in accordance with the theory, namely first awareness raising, the Mojokerto Regency Diskominfo carried out